2014
DOI: 10.1002/chem.201304229
|View full text |Cite
|
Sign up to set email alerts
|

Calcite Microneedle Arrays Produced by Inorganic Ion‐Assisted Anisotropic Dissolution of Bulk Calcite Crystal

Abstract: Besides studies on the mineralization process, research on the demineralization of minerals provides another way to understand the crystallization mechanism of biominerals and fabricate crystals with complicated morphologies. The formation of ordered arrays of c-axis-oriented calcite microneedles with a tri-symmetric structure and lengths of more than 20 μm was realized on a large scale for the first time through anisotropic dissolution of calcite substrates in undersaturated aqueous solution in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…This is consistent with differences in both dissolution rates, measured from in situ flow-through calcite dissolution experiments using atomic force microscopy (AFM) [22,49,66], and atypical surface morphological features development, as in the presence of NH 4 Cl background ions, which lead to spicule formation on {104} calcite surfaces [67].…”
Section: Influence Of Background Electrolyte Concentrationsupporting
confidence: 81%
“…This is consistent with differences in both dissolution rates, measured from in situ flow-through calcite dissolution experiments using atomic force microscopy (AFM) [22,49,66], and atypical surface morphological features development, as in the presence of NH 4 Cl background ions, which lead to spicule formation on {104} calcite surfaces [67].…”
Section: Influence Of Background Electrolyte Concentrationsupporting
confidence: 81%
“…Previous experiments have focused on the use of dissolution strategies to create calcite crystals with surface patterns. Calcite nanoshoot arrays were created via gentle dissolution in undersaturated solutions in the presence of a few selected additives -ammonium iodide and sulfate, 24 ammonium chloride and acetate, 9 and formamide 10 -where this led to nanoshoots with high aspect ratios. Under these conditions dissolution leads to the formation of multiple etch pits over the crystal surface which subsequently increase in size and depth.…”
Section: Additive-directed Changes In Morphology and Surface Patternsmentioning
confidence: 99%
“…7,8 Notably, calcite surfaces patterned with nanoshoots have been generated in the presence of additives using dissolution protocols. 9,10 Again, the surfaces structures formed are expected to reflect the modes of interaction of the additives with the crystal, such that it should be possible to program different surface topographies based on an understanding of the crystal/additive interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66] Our previous studies have shown that microneedles along the c-axis may form via oriented dissolution of geological calcite and biogenic calcite minerals in the presence of additive molecules. [67][68][69][70][71][72] Considering the very good biological compatibility, high mechanical properties, ease of synthesis, and high surface area, the calcite microneedle arrays formed on calcite via oriented dissolution are supposed to be good substrates for transdermal delivery. Oriented dissolution is a very convenient and simple method to prepare microneedle arrays, in comparison to the complicated synthetic methods for microneedle-based transdermal delivery such as lithography, electroplating, and wet and dry etching.…”
Section: Introductionmentioning
confidence: 99%